2016
DOI: 10.1289/ehp.1509779
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Aneuploidy in Faroese Men with Lifetime Exposure to Dichlorodiphenyldichloroethylene ( p , -DDE) and Polychlorinated Biphenyl (PCB) Pollutants

Abstract: Background:Although it is known that sperm aneuploidy contributes to early pregnancy losses and congenital abnormalities, the causes are unknown and environmental contaminants are suspected.Objectives:Our goal was to evaluate associations between lifetime exposure to organochlorines, specifically dichlorodiphenyldicholorethylene (p,p´-DDE) and polychlorinated biphenyls (PCBs), and sperm aneuploidy in men from the general population of the Faroe Islands, a population with a known history of organochlorine expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Chromosomal aneuploidy, DNA damage rates and abnormal morphology in spermatozoa are higher in infertile individuals and may contribute to early pregnancy loss (recurrent miscarriage), birth and developmental defects or other consequences for their offspring later in life (Andreescu et al., ; Kohn, Kohn, Darilek, Ramasamy, & Lipshultz, ; Palermo et al., ; Perry et al., ). Fluorescence in situ hybridisation (FISH) analysis of sperm chromosomes was performed for patients with poor semen quality, recurrent pregnancy loss or recurrent implantation failure and spinal cord injury (anejaculation) (Andreescu et al., ; Kohn et al., ; Palermo et al., ; Perry et al., ; Qiu, Wang, Zhang, & Zhang, ; Qiu, Wang, Zhang, Li, et al., ). To date, no reports have been published about changes in sperm chromosome ploidy, sperm membrane and DNA integrity and AA under testicular heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal aneuploidy, DNA damage rates and abnormal morphology in spermatozoa are higher in infertile individuals and may contribute to early pregnancy loss (recurrent miscarriage), birth and developmental defects or other consequences for their offspring later in life (Andreescu et al., ; Kohn, Kohn, Darilek, Ramasamy, & Lipshultz, ; Palermo et al., ; Perry et al., ). Fluorescence in situ hybridisation (FISH) analysis of sperm chromosomes was performed for patients with poor semen quality, recurrent pregnancy loss or recurrent implantation failure and spinal cord injury (anejaculation) (Andreescu et al., ; Kohn et al., ; Palermo et al., ; Perry et al., ; Qiu, Wang, Zhang, & Zhang, ; Qiu, Wang, Zhang, Li, et al., ). To date, no reports have been published about changes in sperm chromosome ploidy, sperm membrane and DNA integrity and AA under testicular heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies indicated that exposure to agrochemicals is associated with human aneuploidy. For example, exposure to organochlorines has been linked to sperm aneuploidy in men from the general population [13][14][15]. Similarly, exposure to organophosphate insecticides (OP) [16], air pollutants [17,18], and pyrethroids [19,20] were associated with chromosomal abnormalities in human reproductive cells.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the level of detecting sperm aneuploidies and working to understand their role in normal reproduction and ARTs, paternal aging and the impact of the environment continue to attract attention given the evidence showing decreased fertility in many male populations around the world. There is now good evidence to support an environmental impact [4]. And adding to the conundrum at hand is the growing body of literature identifying epigenetic disturbances prior to or during lifespan of males that play out as transgenerational patterns of inheritance appearing in offspring from exposed individuals [5].…”
mentioning
confidence: 99%